Pathology of Fibrosis in Crohn's Disease—Contribution to Understanding Its Pathogenesis - Zidar, Nina; Langner, Cord; Jerala, Miha; Boštjančič, Emanuela; Drobne, David; Tomažič, Aleš (Frontiers in Medicine, 2020)
Background Despite significant progress in the research of fibrosis in various organs, fibrosis remains a poorly understood complication of Crohn’s disease (CD). We analyzed pathologic features of fibrosis and inflammation in CD and compared them with the normal bowel, aiming to clarify whether fibrosis in CD pathogenetically resembles fibrosis in other organs. Methods Resection specimens from 30 patients with CD were included. Normal bowel from resection specimens of colorectal carcinoma was used for comparison. Trichrome Masson staining, immunohistochemistry for α-smooth muscle actin, fibroblast activation protein, CD34 and erg, in situ hybridization for TGF-β1 and analysis of selected fibrosis-related microRNAs were performed. Results In normal bowel, CD34-positive fibroblasts/pericytes were detected in the submucosa and subserosa, particularly around blood vessels. In CD, fibrosis prevailed in the submucosa and subserosa, together with proliferation of myofibroblasts and disappearance of CD34-positive fibroblasts/pericytes. TGF-β1 was present in the lamina propria in normal bowel and CD, and in deeper parts of the bowel wall in CD. MicroRNAs miR-29c, miR-155 miR-150 and miR-155, which have been demonstrated to contribute to fibrosis in various organs, showed significant deregulation in CD. Conclusions Distribution of fibroblasts/pericytes in the submucosa and subserosa of normal bowel, their disappearance in fibrosis in CD, together with the appearance of myofibroblasts, suggest that fibroblasts/pericytes are the most likely source of myofibroblasts in CD. Furthemore, fibrosis-related microRNAs showed deregulation in fibrotic areas. Pathogenesis of fibrosis in CD is thus comparable to fibrosis in other organs, in which myofibroblasts are the key effector cells, and pericytes have emerged as the main origin of myofibroblasts. Fibrosis in CD should be regarded as a result of (over)response of the bowel wall to the presence of inflammation in deep structures of the bowel wall, presenting another example of a common pathogenetic pathway of fibrosis development.